PENDAMPINGAN LITERASI DIGITAL PADA REMAJA UNTUK MENCAPAI RUANG SEHAT DALAM PENGGUNAAN MEDIA - Desmiati, Desmiati; Risma Oviantari, Risma; Ramadhan, Fitria Gumilang; Lestari, Ayu Dewi; Kartiko, Setiyo (Commsphere: Jurnal Ilmu Komunikasi, 2023)
Orphanage have smartphones and use their gadgets without guidance, so they still need to understand media exposure. They also need to learn about the limits of using media. Therefore, this digital literacy activity aims to provide training and digital literacy assistance regarding Healthy Spaces in Using Media by using several methods: brainstorming, games, group discussions, and reflective discussions. The results of this literacy activity have a positive impact on participants, namely that participants can group and understand the excellent use of social media as well as the negative impacts of their use of social media. Keywords: Digital literacy, Youth, Influence, Healthy Space